English Content-Based Approaches to Teaching Accounting - Pablo Moreno Alemay (Universidad de La Sabana, 2010)
This article illustrates the application of strategies on the part of the lecturer to teach a course of accounting in English to non-native English speakers. The following approaches proved to be the most useful: students realizing the importance of acquiring technical vocabulary in English; applying theory during the class as a language strategy; using different bibliographic sources such as journals, books and websites; writing papers which demonstrate student's comprehension; communicating theory utilizing visual tools such as graphs, tables, beamer presentations; progressively reapplying the same financial procedures to more sophisticated settings with increasingly more text; consolidating a strong relationship of cooperation between the lecturer and the Foreign Language Department. This is a process of continuous improvement, hence the need to share results with other instructors and to observe similar experiences from different universities.